Peran Quality Control Dalam Meningkatkan Kualitas Produk Perusahaan Sepatu Adidas (Studi Pada Departemen Quality Integration Program PT. Parkland World Indonesia Jepara) - Zahra, Salma Izdihar; Sutejo, Bambang; Sumiyati, Sumiyati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research was conducted in Jepara Regency, Central Java Province. This study aims to determine the application of employee quality discipline at PT. PARKLAND WORLD INDONESIA JEPARA and know how to increase employee performance productivity to create superior Human Resources and products. This research uses descriptive qualitative research, with the formulation of the problem in the form of a case study. In determining the informants researchers used purposive sampling or sampling technique of data sources with certain considerations. With a total of 6 informants which include : QC Toolgate (Operator), RQC (Leader), QPA (Supervisor), Procedure Staff, Production Supervisor, PPIC Supervisor. Data analysis techniques used in this study are data reduction, data display, and conclusion drawing/verification. With the Credibility Test the data is in the form of source triangulation and method triangulation (observation, documentation and in-depth interviews). From the results of this study it can be seen that the Role of Quality Control in Improving Product Quality of Adidas Shoes Company at PT. PARKLAND WORLD INDONESIA JEPARA needs to create superior human resources and products in order to have satisfactory performance so that there are no more disciplinary actions by employees and the role of leadership as the key to the successful implementation of employee work discipline.